Estudio comparativo entre los recursos Laravel 9 y Django para el desarrollo de aplicaciones web. - Villamar Gastesi, Jorge Javier (2022)
Frameworks are considered the most valuable tools for programmers in general, so it favors the development of projects, these tools are open source so the codes can be used over and over again to facilitate the work of the application. Currently there is a great demand for the development of web applications that is why Frameworks come into play, these in many cases are considered templates for developers since it allows the programmer to have the work finished in a shorter time and it can perform tests so that it runs correctly. In this case study, these well-known instruments such as Frameworks are presented, in which it focuses on the comparison of the 2 tools that are Laravel and Django that are intended to be used in the development of web applications.